2014
DOI: 10.1302/0301-620x.96b10.33695
|View full text |Cite
|
Sign up to set email alerts
|

Results of Birmingham hip resurfacing at 12 to 15 years

Abstract: We report a 12- to 15-year implant survival assessment of a prospective single-surgeon series of Birmingham Hip Resurfacings (BHRs). The earliest 1000 consecutive BHRs including 288 women (335 hips) and 598 men (665 hips) of all ages and diagnoses with no exclusions were prospectively followed-up with postal questionnaires, of whom the first 402 BHRs (350 patients) also had clinical and radiological review. Mean follow-up was 13.7 years (12.3 to 15.3). In total, 59 patients (68 hips) died 0.7 to 12.6 years fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
97
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(107 citation statements)
references
References 46 publications
2
97
0
6
Order By: Relevance
“…The Birmingham Hip Resurfacing (BHR) is the most frequently implanted HR device worldwide [22]. The BHR has established 10-15 year outcomes when implanted by designing [14,23] and independent surgeons [12,13,24], and is also supported by registry data [9,25]. Therefore, for proven HR implants, such as the BHR, closer follow-up is recommended in those with ARMD risk factors [26][27][28], whilst less regular follow-up is required for patients with established devices but without these risk factors.…”
Section: Do All Patients Require Follow-up?mentioning
confidence: 99%
“…The Birmingham Hip Resurfacing (BHR) is the most frequently implanted HR device worldwide [22]. The BHR has established 10-15 year outcomes when implanted by designing [14,23] and independent surgeons [12,13,24], and is also supported by registry data [9,25]. Therefore, for proven HR implants, such as the BHR, closer follow-up is recommended in those with ARMD risk factors [26][27][28], whilst less regular follow-up is required for patients with established devices but without these risk factors.…”
Section: Do All Patients Require Follow-up?mentioning
confidence: 99%
“…Metal-on-metal hip resurfacing has been considered an effective way to treat young and active patients with endstage osteoarthritis since the 1990s [9,13,14,30,31]. However, aseptic failure of the femoral component (component loosening or femoral neck fracture) has been reported as one of the main modes of failure, particularly in the early reports [3,12,19,21,23,25].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Bozic et al [8] compared the clinical effectiveness and cost-effectiveness of MoM hip resurfacing to THR and concluded that MoM hip resurfacing could be clinically advantageous and cost-effective in younger men and women. Daniel et al [9] reported a 12-to 15-year implant survival assessment of a prospective single-surgeon series of Birmingham Hip Resurfacing (BHR) and showed that the performance of the BHR is good at 12-to 15-year follow up, especially for male patients under 50 years. Matharu et al [10] reported the long-term survival and functional outcome of the BHR in patients aged o50 years at operation and stated that the BHR provides excellent survival and functional results in men into the second decade, with good results achieved in appropriately selected women.…”
Section: Introductionmentioning
confidence: 99%